Discovery of new eremophilanes from the marine-derived fungus Emericellopsis maritima BC17 by culture conditions changes: evaluation of cytotoxic and antimicrobial activities - Virués-Segovia, Jorge R.; Pinedo, Cristina; Zorrilla, David; Sánchez-Márquez, Jesús; Sánchez, Pilar; Ramos, María C.; de la Cruz, Mercedes; Aleu, Josefina; Durán-Patrón, Rosa (Frontiers in Marine Science, 2024)
In our previous studies, the marine-derived fungus Emericellopsis maritima BC17 was found to produce new eremophilane-type sesquiterpenoids on solid media. In order to explore its potential to produce more metabolites, E. maritima BC17 was subjected to a one strain-many compounds (OSMAC) analysis leading to the discovery of three new eremophilanes (1-3) and fourteen known derivatives (4-17) in the liquid media Czapek Dox and PDB. Their structures were established by extensive analyses of the 1D and 2D NMR, and HRESIMS data, as well as ECD data for the assignment of their absolute configurations. Antitumoral and antimicrobial activities of the isolated metabolites 1, 3, 11, and 15 were investigated. PR toxin 3-deacetyl (15) exhibited cytotoxic activity against HepG2, MCF-7, A549, A2058 and Mia PaCa-2 human cancer cell lines with IC50 values ranging from 2.5 to 14.7 µM. In addition, 15 exhibited selective activity against methicillin-sensitive Staphylococcus aureus ATCC29213 at the highest concentration tested of 128 µg/mL.